Water and chloride transport in a fine-textured soil profile in a feedlot pen - Veizaga, Emiliano Andrés (2015)
Cattle feeding in feedlot pens produces large amounts of manure and animal urine. Manure solutions resulting from surface runoff are composed of numerous chemical constituents whose leaching causes salinization of the soil profile. There is a relatively large number of studies on preferential flow characterization and modeling in clayed soils. However, research on water flow and solute transport derived from cattle feeding operations in fine-textured soils under naturally occurring precipitation events is less frequent. A field monitoring and modeling investigation was conducted at two plots on a fine-textured soil near a feedlot pen in Argentina to assess the potential of solute leaching into the soil profile. Soil pressure head and chloride concentration of the soil solution were used in combination with HYDRUS-1D numerical model to simulate water flow and chloride transport resorting to the concept of mobile/immobile—MIM water for solute transport. Pressure head sensors located at different depths registered a rapid response to precipitation suggesting the occurrence of preferential flow-paths for infiltrating water. Cracks and small fissures were documented at the field site where the % silt and % clay combined is around 94%. Chloride content increased with depth for various soil pressure head conditions, although a dilution process was observed as precipitation increased. The MIM approach improved numerical results at one of the tested sites where the development of cracks and macropores is likely, obtaining a more dynamic response in comparison with the advection–dispersion equation.